Respiratory Dysfunction and Sleep-Disordered Breathing in Children With Myasthenia Gravis. (August 2020) - Katzberg, Hans D.; Vajsar, Jiri; Vezina, Kevin; Qashqari, Heba; Selvadurai, Sarah; Chrestian, Nicholas; Khayat, Abdullah; Ryan, Clodagh M.; Narang, Indra
Objectives: The purpose of this study was to prospectively evaluate sleep patterns and the presence of sleep-disordered breathing in children with myasthenia gravis. We further aimed to examine the relationship between sleep and daytime respiratory function using spirometry tests including upright and supine forced vital capacity, sniff nasal inspiratory pressure, and maximal inspiratory pressure. Methods: Eleven children between 3 and 18 years old with confirmed myasthenia gravis were recruited from The Hospital for Sick Children Neuromuscular Clinic in this prospective observational study. After informed consent was obtained, patients underwent a comprehensive clinical assessment with collection of anthropometric data. Following this, all subjects performed pulmonary function tests, overnight polysomnography and completed the Epworth Sleepiness Scale questionnaire. Results: Two of eleven children who reported no symptoms of sleep disordered breathing were diagnosed with mild to moderate obstructive sleep apnea. Pulmonary function tests showed abnormal maximal inspiratory pressure in 6 of 11 patients, whereas seated forced vital capacity as well as seated to supine forced vital capacity ratios were normal in the entire group. Conclusions: In our small group of pediatric myasthenia gravis subjects, there was an unexpected finding of obstructive sleep apnea in 2 of the 11 patients studied. Maximal inspiratory pressure appears to be a more sensitive method of detecting abnormalities compared to upright or seated forced vital capacity. A larger multicenter study is needed to validate our findings and to determine the impact of obstructive sleep apnea in the pediatric myasthenia gravis population as well as risk factors associated with sleep disordered breathing.